Quantification of edema in edematous severe acute malnutrition children aged 6 months to 5 years - Suman, Rameshwar L; Singla, Sanjay; Chaudhry, Chakshu; Ninama, Rameshwar; Sharma, Bharat Lal; Goyal, Suresh (Indian Journal of Child Health, 2018)
Background: Malnutrition is rampant in India, and edematous severe acute malnutrition (SAM) is associated with high morbidity and mortality. Clinical grading of edema in these children is known, but still, no quantification has been described. Objective: The objective of this study was to quantify the edema in children with edematous SAM (E-SAM). Materials and Methods: This prospective study was conducted over a period of 1 year in 2016 at a malnutrition treatment center of tertiary hospital attached to a medical college. 50 children were selected with E-SAM between 6 months and 5 years of age. The sick children, needing intensive care unit care and having edema other than nutritional cause, were excluded from the study. These children were examined daily for any change in the status of edema by comparing the change in the weight, which was taken using electronic weighing scale. The weight at which child has no edema and no fall in weight for 2 consecutive days was defined as dry weight of the child. All the children were evaluated regarding the onset of loss of edema, days taken for complete disappearance of edema, weight loss per day, mean loss of weight, etc. Results: Of 50 children with E-SAM, 28 were male and 22 were females. Mean age of children was 16.5±11.04 months. The admitted children had +2 edema (26%), followed by +3 edema (17%), while only 7 (14%) children had +1 edema. The mean age of moderate-to-severe edematous children was 13 months. These children started losing edema by day 3 (3.22±0.9) and the mean number of days for complete disappearance of edema was 10.02±2.8 days. The mean percent weight loss was 1% per day and did not vary with different grades of edema (p>0.5). The percentage loss of total weight was maximum for children with +3 edema being 13%, followed by 10% in +2, and 5% in +1 edema which was statistically significant (p=0.004). Conclusions: E-SAM children have grade +1, +2, and +3 edema which are equivalent to 5%, 10%, and >10% over to their actual weight, respectively, and younger children are more susceptible to moderate-to-severe edema.